Liquid chromatography-tandem mass spectrometry for determination of fingolimod and its active metabolite fingolimod phosphate in whole blood of patients with multiple sclerosis - Pesakova, Veronika; Brozmanova, Hana; Sistik, Pavel; Kusnirikova, Zuzana; Kacirova, Ivana; Grundmann, Milan (Biomedical chromatography : BMC, 2024)
Fingolimod is an oral drug for the escalation of treatment of relapsing-remitting multiple sclerosis in patients with persistent disease activity on first-line drugs or in patients with rapidly progressive severe relapsing-remitting multiple sclerosis. An ultra-high-performance liquid chromatography-tandem mass spectrometry method for determining the concentrations of fingolimod and its active metabolite fingolimod phosphate in whole blood has been developed and validated. The advantages of this method are the easy, fast and cheap sample preparation using protein precipitation from blood with a mixture of acetonitrile-methanol (40:60, v/v). Chromatographic separation was performed on a ultra-high performance liquid chromatography BEH C18 1.7 μm (100 × 2.1 mm) column. Two modes of ionization, electrospray ionization and atmospheric pressure chemical ionization, were tested and compared. For validation, the electrospray ionization mode was chosen. As internal standard, isotopically labeled fingolimod-D4 was used to quantify the analytes. The method was validated according to the rules of the European Medicines Agency. The coefficients of variation for fingolimod were in the range of 1.13-11.88%, and the recovery was 98.80-106.00%. The coefficients of variation for fingolimod phosphate were in the range of 2.73-9.31%, and the recovery was 90.08-107.00%. The method is quite easy and fast and can be used for routine analysis.
Keywords: lineární modely; Chromatography, High Pressure Liquid; Limit of Detection; limita detekce; Chromatography, Liquid; Humans; Tandem Mass Spectrometry; Multiple Sclerosis; Female; dospělí; lidé; imunosupresiva; reprodukovatelnost výsledků; tandemová hmotnostní spektrometrie; fingolimod hydrochlorid; Adult; Immunosuppressive Agents; ženské pohlaví; chromatografie kapalinová; roztroušená skleróza; Male; Reproducibility of Results; Linear Models; Fingolimod Hydrochloride; mužské pohlaví; vysokoúčinná kapalinová chromatografie